How to build the optimal magnet assembly for magnetocaloric cooling: Structural optimization with isogeometric analysis - Michael Wiesheu; Melina Merkel; Tim Sittig; Dimitri Benke; Max Fries; Sebastian Schöps; Oliver Weeger; Idoia Cortes Garcia (International Journal of Refrigeration, 2023)

Migration of styrene oligomers from food contact materials: in silico prediction of possible genotoxicity - Elisa Beneventi; Christophe Goldbeck; Sebastian Zellmer; Stefan Merkel; Andreas Luch; Thomas Tietz (Archives of Toxicology, 2022)
Styrene oligomers (SO) are well-known side products formed during styrene polymerization. They consist mainly of dimers (SD) and trimers (ST) that have been shown to be still residual in polystyrene (PS) materials. In this study migration of SO from PS into sunflower oil at temperatures between 5 and 70 °C and contact times between 0.5 h and 10 days was investigated. In addition, the contents of SD and ST in the fatty foodstuffs créme fraiche and coffee cream, which are typically enwrapped in PS, were measured and the amounts detected (of up to 0.123 mg/kg food) were compared to literature data. From this comparison, it became evident, that the levels of SO migrating from PS packaging into real food call for a comprehensive risk assessment. As a first step towards this direction, possible genotoxicity has to be addressed. Due to technical and experimental limitations, however, the few existing in vitro tests available are unsuited to provide a clear picture. In order to reduce uncertainty of these in vitro tests, four different knowledge and statistics-based in silico tools were applied to such SO that are known to migrate into food. Except for SD4 all evaluated SD and ST showed no alert for genotoxicity. For SD4, either the predictions were inconclusive or the substance was assigned as being out of the chemical space (out of domain) of the respective in silico tool. Therefore, the absence of genotoxicity of SD4 requires additional experimental proof. Apart from SD4, in silico studies supported the limited in vitro data that indicated the absence of genotoxicity of SO. In conclusion, the overall migration of all SO together into food of up to 50 µg/kg does not raise any health concerns, given the currently available in silico and in vitro data.

MCCP: are medium-chain chlorinated paraffins of concern for humans? - Sebastian Zellmer; Lisa Heiserich; Oliver Kappenstein; Stefan Merkel; Agnes Schulte; Andreas Luch (Archives of Toxicology, 2020)

Aggregated aluminium exposure: risk assessment for the general population - Thomas Tietz; Ariane Lenzner; Anna Elena Kolbaum; Sebastian Zellmer; Christian Riebeling; Rainer Gürtler; Christian Jung; Oliver Kappenstein; Jutta Tentschert; Michael Giulbudagian; Stefan Merkel; Ralph Pirow; et al. (Archives of Toxicology, 2019)
Aluminium is one of the most abundant elements in earth’s crust and its manifold uses result in an exposure of the population from many sources. Developmental toxicity, effects on the urinary tract and neurotoxicity are known effects of aluminium and its compounds. Here, we assessed the health risks resulting from total consumer exposure towards aluminium and various aluminium compounds, including contributions from foodstuffs, food additives, food contact materials (FCM), and cosmetic products. For the estimation of aluminium contents in foodstuff, data from the German “Pilot-Total-Diet-Study” were used, which was conducted as part of the European TDS-Exposure project. These were combined with consumption data from the German National Consumption Survey II to yield aluminium exposure via food for adults. It was found that the average weekly aluminium exposure resulting from food intake amounts to approx. 50% of the tolerable weekly intake (TWI) of 1 mg/kg body weight (bw)/week, derived by the European Food Safety Authority (EFSA). For children, data from the French “Infant Total Diet Study” and the “Second French Total Diet Study” were used to estimate aluminium exposure via food. As a result, the TWI can be exhausted or slightly exceeded—particularly for infants who are not exclusively breastfed and young children relying on specially adapted diets (e.g. soy-based, lactose free, hypoallergenic). When taking into account the overall aluminium exposure from foods, cosmetic products (cosmetics), pharmaceuticals and FCM from uncoated aluminium, a significant exceedance of the EFSA-derived TWI and even the PTWI of 2 mg/kg bw/week, derived by the Joint FAO/WHO Expert Committee on Food Additives, may occur. Specifically, high exposure levels were found for adolescents aged 11–14 years. Although exposure data were collected with special regard to the German population, it is also representative for European and comparable to international consumers. From a toxicological point of view, regular exceedance of the lifetime tolerable aluminium intake (TWI/PTWI) is undesirable, since this results in an increased risk for health impairments. Consequently, recommendations on how to reduce overall aluminium exposure are given.

Diabetes and atrial fibrillation: stratification and prevention of stroke risks - Stephan v Bandemer; Sebastian Merkel; Anna Nimako-Doffour; Mattias M Weber (EPMA Journal, 2014)